Identification of Mechanical Strength for Mixture of Thermoset Polyester with Thermoset Vinyl Ester due to Bending Load - Nusyirwan Adnan; H. Abral; Dahlan H; E. Staria (Universitas Muhammadiyah Yogyakarta, 2022)
Pada penelitian ini dilakukan upaya untuk meningkatkan ketangguhan mekanis Unsaturated Polyester (UP) dengan menambahkan Thermoset Vinyl Ester (VE) dan Methyl Methacrylate (MMA). Untuk menunjukkan tingkat ketangguhan material dilakukan pengujian dengan memberikan beban lentur sampai material tersebut putus. Hasil pengujian menunjukkan bahwa campuran 40 % wt VE dan 10% wt MMA pada material UP menghasilkan peningkatan sifat ketangguhan material dari pengujian bending stress pada spesimen dengan variasi komposisi polyester dan vinyl ester dengan hand lay-up. Nilai tegangan lentur tertinggi terdapat pada komposisi 60% polyester dan 40% vinyl ester yaitu sebesar 126,88 MPa (meningkat 16 % dari polyester murni).In this study, an attempt was made to increase the mechanical toughness of unsaturated polyester (UP) by adding Thermoset Vinyl Ester (VE) and Methyl Methacrylate (MMA). A test is carried out to show the level of toughness of the mechanical properties of the above material by applying a flexural load until the material breaks. The test results showed that a mixture of 40% wt VE and 10% wt MMA in UP material resulted in an increase in the toughness properties of the material from the bending stress test on specimens with variations in the composition of polyester and vinyl ester with hand lay-up. The highest flexural stress value is found in the composition of 60% polyester and 40% vinyl ester, which is 126.88 MPa (an increase of 16% from pure polyester).